(untitled) (The Agriculturists, 2012)
Field experiments were conducted during 2007-2010 to evaluate the agro-economic productivity of BRRI Aman rice varieties and Rabi vegetables at the Bangladesh Rice Research Institute (BRRI) in silty clay loam soil. Five Aman rice varieties having different growth durations and three winter vegetables viz., tomato, red amaranth and bush bean were evaluated in split plot design with three replications. Mungbean was grown in Kharif-I season. Rice varieties did not differ significantly in terms of grain yield (t ha-1). Among the three vegetables, the yields of tomato, red amaranth and bush bean were 35.02, 7.53 and 4.33 t ha-1, respectively. Average yield of Mungbean was 0.89 t ha-1. In case of rice equivalent yield (REY), Tomato-Mungbean-BRRI dhan33 cropping pattern produced comparatively high average REY (29.95 t ha-1) followed by Tomato-Mungbean-BRRI dhan39 (27.33 t ha-1) cropping pattern. Among the tested cropping patterns, Tomato-Mungbean-BRRI dhan33 and Tomato-Mungbean-BRRI dhan39 were more profitable than other patterns. DOI: http://dx.doi.org/10.3329/agric.v10i2.13149 The Agriculturists 2012; 10(2) 120-126